Current and emerging biologic therapies for allergic rhinitis and chronic rhinosinusitis. (2nd June 2020) - Licari, Amelia; Castagnoli, Riccardo; De Filippo, Maria; Foiadelli, Thomas; Tosca, Maria Angela; Marseglia, Gian Luigi; Ciprandi, Giorgio
ABSTRACT: Introduction : Allergic rhinitis and chronic rhinosinusitis, with and without nasal polyps, are the most common chronic inflammatory diseases of the upper airways. They both cause relevant respiratory symptoms and a substantial detriment to patients' quality of life, mainly in uncontrolled and severe patients. Areas covered : This review aims to present the most recent evidence on current and emerging biologic therapies for allergic rhinitis and chronic rhinosinusitis and discuss their potential implementation in clinical practice. To select relevant literature for inclusion in this review, we conducted a literature search using the PubMed database, using terms 'biologics OR biological agents', 'allergic rhinitis' and 'chronic rhinosinusitis'. The literature review was performed for publication years 2009–2019, restricting the articles to humans and English language publications. Expert opinion : Biological therapies represent a potential step forward in providing individualized care for all patients with uncontrolled severe upper airway diseases. Biologics recently showed promising results for the treatment of severe uncontrolled allergic rhinitis and chronic rhinosinusitis with nasal polyps with or without associated asthma. Endotyping inflammatory pathways and identifying related biomarkers remain the major challenge for positioning biologics in the care pathway of chronic respiratory diseases.